NITROGEN FERTILIZATION ON BIOMASS YIELD AND CHEMICAL COMPOSITION OF MOMBAÇA GRASS ON THE FIRST PLATEAUX OF PARANÁ - MAZZA, Lorena de Miranda; PÔGGERE, Giovana Clarice; FERRARO, Fernanda Pereira; RIBEIRO, Camila Basto; CHEROBIM, Verediana Fernanda; MOTTA, Antonio Carlos Vargas; MORAES, Anibal de (Scientia Agraria, 2009)
The majority of Brazilian livestock is raised under pasture which usually has low productivity. This is due to both low biomass offer and low quality of pastures. The objective of this study was to evaluate the Nitrogen fertilization on yield and quality of Mombaça grass (Panicum maximum cv. Mombaça). The experiment was carried out at Canguiri Experimental Station located Pinhais county-Parana state, belonging to Federal University of Paraná. An oxissol with high organic matter content, low acidic, and without limitation of available P and K was used for the study. The experimental design was a randomized complete block with four replications and five N rate treatments (0, 85, 170, 320 e 510 kg of N ha-1) applied broadcast in the first week of November 2007. The pasture was evaluated for yield dry matter (DM), chlorophyll leaf contents, and total concentration of nitrogen and carbon. The nitrogen fertilization resulted in great improvement on DM and protein yield, varying from 585 to 10.310 and from 45 to 1279 kg ha-1, after 85 and 161 days fertilization application, respectively. The DM increment showed to be linear with 19 kg DM for each kg N applied. Each kg N applied also provided the following linear variation: 0,5x10-5 mg kg-1 - chlorophyll leaf content; 0,015 g kg-1 - N concentration; 2,52 kg ha-1 - total protein yield; 7,98 kg ha-1 total C yield, and -0,025 - C/N ratio. The nitrogen fertilization enhanced productivity and forage quality for developed grass under good condition of soil fertility. Also, it enhances the C input to pasture system.